Kedudukan dan Hikmah Mahar dalam Perkawinan - Maki, Leo Perkasa (Syakhsiyah Jurnal Hukum Keluarga Islam, 2022)
The dowry (mahr) is a significant element in the marriage contract, holding a distinct position in Islamic law. This study aims to analyze the position of the dowry in marriage and uncover the wisdom behind its provision. Using a normative-juridical approach and literature review, this research explores the legal basis of the dowry in the Qur'an, Hadith, and opinions of Islamic scholars. The study also highlights the social and religious implications of the dowry, including its role as a symbol of respect for women and as a form of the husband's responsibility. The findings indicate that the dowry is not merely a material gift but carries deep spiritual and social meanings, serving to strengthen the marital bond and protect the rights of the wife. The dowry also reflects the husband's responsibility in ensuring the welfare of his family. In conclusion, the dowry's position in marriage is highly significant from both Islamic legal and societal perspectives, and its provision holds broad wisdom for both parties in marriage.